2016
DOI: 10.1589/jpts.28.2474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trunk stability on isometric knee extension muscle strength measurement while sitting

Abstract: [Purpose] This study aimed to investigate the effect of trunk stability on isometric knee extension muscle strength measurement while sitting by performing simultaneous measurements with a handheld dynamometer (HHD) and an isokinetic dynamometer (IKD) in the same seated condition. [Subjects and Methods] The subjects were 30 healthy volunteers. Isometric knee extension muscle strength was simultaneously measured with a HHD and an IKD by using an IKD-specific chair. The measurement was performed twice. Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…These previous studies have suggested that measurement value of IKD is higher than that of HHD, and HHD and IKD are related although the conditions of measurement position for comparing are not similar. In contrast, in the same sitting condition with trunk fixation, no significant difference was reported between the measurements obtained using HHD and IKD 22) . The difference between the measurement values of HHD and IKD was considered to be attributed to the different measurement conditions with respect to the presence or absence of trunk fixation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These previous studies have suggested that measurement value of IKD is higher than that of HHD, and HHD and IKD are related although the conditions of measurement position for comparing are not similar. In contrast, in the same sitting condition with trunk fixation, no significant difference was reported between the measurements obtained using HHD and IKD 22) . The difference between the measurement values of HHD and IKD was considered to be attributed to the different measurement conditions with respect to the presence or absence of trunk fixation.…”
Section: Discussionmentioning
confidence: 59%
“…However, a previous study on validity was conducted using different measurement postures or different sitting conditions. In the same postural setting with the participant in the sitting position fixed with straps, Hirano et al 22) reported that the measurement values between the measuring equipment was not significantly different and that the HHD and IKD were correlated (r=0.96 to 0.98, p<0.01).…”
Section: Introductionmentioning
confidence: 99%
“…The problem with the HHD measuring lower peak forces than other methods have also been shown in comparison with an isokinetic dynamometer [38,39], however, this is not a universal finding [27,40]. It could be that the difference between a HHD and an isokinetic dynamometer is affected by trunk stability, since when stabilising the trunk during a HHD measurement, the methods seem to measure the same [24]. Within the healthy population, similar to our findings, fixating the HHD against the bunk leg instead of the participant's leg ensures that the results of the fixated HHD and an isokinetic dynamometer, or in our case a load cell, will not statistically differ.…”
Section: Discussionmentioning
confidence: 98%
“…The make method can be done either with manual resistance or with fixation of the HHD. Even though manual resistance is the most utilised way of using a HHD [19,22,23], the reliability and validity of this technique compared to an isokinetic dynamometer or to a load cell vary markedly between studies [12,19,24]. This could, at least partly, be explained by a lack of a standardised test procedure [19] but it could also be a result of difficulties to manually resist the force produced by the tested limb.…”
Section: Introductionmentioning
confidence: 99%
“…However, because these dynamometers are extensive and too large, use in sports-medicine practices are limited 1 ) . In recent years, the validity and reliability of simple handheld dynamometers have been investigated for alternative measurements of muscle strength 2 , 3 ) . Significant correlation coefficients between the values obtained using handheld dynamometers and isometric dynamometers have been reported 2 , 4 , 5 ) .…”
Section: Introductionmentioning
confidence: 99%